Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Ru - Thúy, Kim (Libre Expression,une compagnie de Quebecor Media, 2009)
« "Le paradis et l'enfer s'étaient enlacés dans le ventre de notre bateau. Le paradis promettait un tournant dans notre vie, un nouvel avenir, une nouvelle histoire. L'enfer, lui, étalait nos peurs : peur des pirates, peur de mourir de faim, peur de s'intoxiquer avec les biscottes imbibées d'huile à moteur, peur de manquer d'eau, peur de ne plus pouvoir se remettre debout, peur de devoir uriner dans ce pot rouge qui passait d'une main à l'autre, peur que cette tête d'enfant galeuse ne soit contagieuse, peur de ne plus jamais fouler la terre ferme, peur de ne plus revoir le visage de ses parents assis quelque part dans la pénombre au milieu de ces deux cents personnes." Ru est le récit d'une réfugiée vietnamienne, une boat people dont les souvenirs deviennent prétexte tantôt à l'amusement, tantôt au recueillement, oscillant entre le tragique et le comique, entre Saigon et Granby, entre le prosaïque et le spirituel, entre les fausses morts et la vraie vie. »– Quatrième de couverture.
Section: 144 pages ; 23 cm
Keywords: amériques; approches et analyses; arts; asie; boat people; canada; cours; discipline; histoire et politique; immigration; lit3220; littérature; premier cycle; québec; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; vietnam; écriture des femmes*; études littéraires